Indian Ocean networks of Daʿwa, Tijāra, and Khizāna: The Bohras as Manuscript Agents in Yemen - Olly Akkerman (Arabian Humanities)
This article focuses on the question of the circulation of manuscripts and khizānāt al-kutub (book treasuries) between the Arabian Peninsula and the Indian Subcontinent in the early modern period. More specifically, it explores how a mercantile Shiʿi Ismaʿili community, known as the Ṭayyibī Bohras, operated between Gujarat and Yemen as merchant tycoons, students, pilgrims, administrators, benefactors, and scholars. Drawing on the content as well as the materiality of sources from the Bohra khizāna, I argue that the Indian Bohras were key actors among the Ismaʿilis in Yemen, politically, economically, and socially, rather than passive students and disciples. Via their communal Indian Ocean networks of daʿwa (community) and tijāra (trade), they played a vital role in facilitating the network of mobility and learning of Indian students to Yemen, as well as financing the daʿwa, and securing its survival in India by sending, copying, and requesting manuscripts overseas, a process which continued well into the nineteenth century.